'She's' who make history : reviewing the historical treatment of black women by four South African scholars. (Historia, 2021)
(A)s Jane Marcus has observed, "She who writes history makes history" - and (to this may be added), she whose activities are visible as history has a kind of power that she whose contributions are placed at the margins of history does not. Changing 'history', ... depends on having that first kind of power; it comes from speaking somewhere other than from the margins, although speaking from the margins has its uses too.
Keywords: History; Power; Marginalized; Women; Black; South Africa